Youth awareness: a survey on mobile gaming addiction concerning physical health performance on young adults in Malaysia / Anis Shahirah Zakaria and Wardatul Hayat Adnan - Zakaria, Anis Shahirah; Adnan, Wardatul Hayat (Universiti Teknologi MARA, 2022)
Mobile gaming has certainly become popular amongst young adults these days especially with the popularity of esports and mobile gaming communities available online recently. Previous studies have highlighted gaming addiction tendencies and mental health issues. However, there were other concerning issues caused by mobile gaming addiction that affects young adults in physical health such as bad posture, obesity, visual impairment, muscular weaknesses, and more. Thus, this study aimed to explore how Malaysian young adults' level of awareness on mobile gaming addiction could affect their physical health performance. Quantitative study method was conducted on Malaysian young adults with the sample of 80 selected through convenience sampling. A questionnaire constructed from multiple past researches to obtain data for the study had helped generate the perfect correlation scores and regression values that indicates the relationship between the research variables of analysis. The result showed perfect correlation value for all variables of analysis. The study also generated the highest regression value for research question 1 at 83% while research questions 2 and 3 were found to have weaker regression value. The significance of this study produces results on whether young adults' awareness regarding physical health had improved and increased the knowledge on adverse health effects related to prolonged mobile gaming. Moreover, studies related to physical health regarding mobile gaming are beneficial for the future generation to prevent mobile gaming addiction.